Impact of Brachial-Ankle Pulse Wave Velocity on Myocardial Work by Non-invasive Left Ventricular Pressure-Strain in Non-hypertensive and Hypertensive Patients With Preserved Left Ventricular Ejection Fraction - Duan, Qin; Zhang, Dongying; Dong, Qian; Liao, Kangla; Yang, Yunjin; Ye, Liu; Ge, Ping; Qin, Shu (Frontiers in Cardiovascular Medicine, 2022)
Objective Data regarding the influence of arterial stiffness on myocardial work (MW) has been scarce. This study was performed to investigate the association between brachial-ankle pulse wave velocity (baPWV) and MW by non-invasive left ventricular pressure–strain in a population of non-hypertensive and hypertensive individuals. Methods Two hundred and eight participants (104 hypertensive and 104 non-hypertensive individuals) were prospectively enrolled into the study. All participants underwent conventional echocardiography, as well as 2D speckle-tracking echocardiography to assess MW by non-invasive left ventricular pressure–strain and global longitudinal strain (GLS). baPWV measurements were made at the same day as the echocardiography. Then, participants were categorized according to baPWV tertiles. Correlation between baPWV and MW were analyzed. Predicting ability of baPWV for abnormal WM was analyzed using receiver operating characteristic (ROC) curve. Results The median baPWV from the low to high tertile groups were 1286.5 (1197.5–1343.5), 1490.0 (1444.5–1544.0), and 1803.8(1708.3–1972.0) cm/s, respectively. In simple linear regression analysis, baPWV had a significant positive association with global work index (GWI), global constructed work (GCW), and global wasted work (GWW), and a negative association with global work efficiency (GWE). The association remained significant after adjusting for major confounding factors in multiple linear regression analysis. The areas under the ROC curve of baPWV for predicting abnormal GWI, GCW, GWW, and GWE were 0.653, 0.666, 0.725, and 0.688, respectively (all p < 0.05). Conclusions BaPWV is significantly associated with all four components of MW using non-invasive left ventricular pressure-strain method in a mixed population of non-hypertensive and hypertensive individuals.